SURFACE TEMPERATURES ON TITAN DURING NORTHERN WINTER AND SPRING - Jennings, D. E.; Cottini, V.; Nixon, C. A.; Achterberg, R. K.; Flasar, F. M.; Kunde, V. G.; Romani, P. N.; Samuelson, R. E.; Mamoutkine, A.; Gorius, N. J. P.; Coustenis, A.; Tokano, T. (IOP PUBLISHING LTD, 2016)
Meridional brightness temperatures were measured on the surface of Titan during the 2004-2014 portion of the Cassini mission by the Composite Infrared Spectrometer. Temperatures mapped from pole to pole during five two-year periods show a marked seasonal dependence. The surface temperature near the south pole over this time decreased by 2 K from 91.7 +/- 0.3 to 89.7 +/- 0.5 K while at the north pole the temperature increased by 1 K from 90.7 +/- 0.5 to 91.5 +/- 0.2 K. The latitude of maximum temperature moved from 19 S to 16 N, tracking the subsolar latitude. As the latitude changed, the maximum temperature remained constant at 93.65 +/- 0.15 K. In 2010 our temperatures repeated the north-south symmetry seen by Voyager one Titan year earlier in 1980. Early in the mission, temperatures at all latitudes had agreed with GCM predictions, but by 2014 temperatures in the north were lower than modeled by 1 K. The temperature rise in the north may be delayed by cooling of sea surfaces and moist ground brought on by seasonal methane precipitation and evaporation.